Step
*
of Lemma
A-rightunit'
∀Val:Type. ∀n:ℕ. ∀AType:array{i:l}(Val;n). ∀T:Type. ∀m:A-map'(array-model(AType)) T.
  ((A-bind'(array-model(AType)) m A-return'(array-model(AType))) = m ∈ (A-map'(array-model(AType)) T))
BY
{ (RepUR ``A-bind' A-return' array-model A-map'`` 0 THEN Auto) }
Latex:
Latex:
\mforall{}Val:Type.  \mforall{}n:\mBbbN{}.  \mforall{}AType:array\{i:l\}(Val;n).  \mforall{}T:Type.  \mforall{}m:A-map'(array-model(AType))  T.
    ((A-bind'(array-model(AType))  m  A-return'(array-model(AType)))  =  m)
By
Latex:
(RepUR  ``A-bind'  A-return'  array-model  A-map'``  0  THEN  Auto)
Home
Index